Relationship between Body Mass Index and Ductus Venosus Doppler Measurements at 11-14 Gestational Weeks - (:unkn) unknown (My University, 2018)
Introduction: In this study, we aimed to investigate the possible causative relationship between maternal obesity and flowpatterns of ductus venosus.Methods: One hundred twenty three pregnant women with a body mass index of 25 or higher and 83 pregnant womenwith body mass index lower than 25 in gestational weeks between 11-14, were included in the present study.Results: The findings showed that there was no statistically significant difference between the two groups for a combinedtest, three-component antenatal tests, second-level ultrasonography. In 12% of the women, loss of a wave and/or inversea wave was noted. In the rest of the women, there were no pathological waves. In 4.8% of women with a BMI less than 25,there was an abnormality in ductus venosus flow pattern, whereas this ratio was 17% in the other group consisted of womenwith BMI higher than 25; and the difference was statistically significant (p=0.008).Discussion and Conclusion: We concluded that maternal hyperglycemia and high body mass index might cause abnormalflow patterns in ductus venosus in pregnancies with normal first-trimester scanning and abnormal flow patterns ofductus venosus.
Keywords: Alerji; Androloji; Anestezi; Biyokimya ve Moleküler Biyoloji; Kalp ve Kalp Damar Sistemi; Klinik Nöroloji; Yoğun Bakım, Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tıbbi Etik; Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak, Burun, Boğaz; Patoloji; Pediatri; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Üroloji ve Nefroloji